(untitled) (Experimental biology, 2025)
This review focuses on the issue of cadmium contamination in agricultural lands, a significant concern in many developing countries, including Kazakhstan. Such contamination is primarily linked to the growth of heavy industries in mining regions, soil pollution from metallurgical plants, emissions from vehicles, and the widespread use of phosphorus fertilizers and pesticides containing cadmium. Heavy metals tend to accumulate around large industrial hubs, contaminating soil, water, and plants. These metals can then enter the food chain via forage plants, affecting animals and humans. Even small amounts of cadmium in the soil can reduce crop yields, inhibit plant growth, and disrupt physiological and biochemical processes. Therefore, it is essential to study how cadmium impacts plants and explore strategies to enhance plant resistance to this metal. This review examines the effects of heavy metals, particularly cadmium, on plant pollution, its accumulation in plant tissues, and its toxic impact on plant growth...